WORK PROGRAM OF MADRASAH COMMITTEE - Isnaini Septemiarti; Widia Yunita (STAI Hubbulwathan Duri, 2019)
This study aims to determine the role of the madrasah committee in improving the quality of madrasah. This research is a qualitative descriptive study. The subjects in this study were the head of the madrasah and the madrasah committee. While the object of this research is the work program of the MTsN 2 Siak madrasah committee for the 2018/2019 academic year. The number of samples in this study were 13 people consisting of 1 madrasah principal and 12 madrasah committees. Data obtained through interviews, observation, and documentation. The results showed that the madrasah committee had played its role and function as a provider of consideration, support and mediator. In the relationship between the head of madrasah and the madrasah committee, it can be linked as coordinative, supportive, evaluative, normative, collaborative, and communicative.